Relationship Between Oxidative Stress Markers and Endothelin-1 Levels in Newborns of Different Gestational Ages - Gospodin Stefanov; Seema Briyal; Gwendolyn Pais; Bhagya Puppala; Anil Gulati (Frontiers Media S.A., 2020)
Oxidative stress results from excessive reactive oxygen species formation and/or inadequate antioxidant defense. Premature and critically ill infants are especially susceptible due to an immature intrinsic antioxidant system that cannot fully compensate for a free radical load. Oxidative stress is also associated with endothelial dysfunction and alterations in Endothelin-1 (ET-1) signaling pathways. However, the effects of the complex interaction between oxidative stress and ET-1 in newborns are not well-understood. The objective of this pilot study was to determine the relationship between levels of common oxidative stress biomarkers [glutathione (GSH), malondialdehyde (MDA)] and ET-1 in newborns of different gestational ages. In a level IV NICU, 63 neonates were prospectively enrolled and divided into groups based on gestational age at birth: Early Preterm (24 0/7-30 6/7 weeks), Late Preterm (31 0/7-36 6/7 weeks), and Term (37 0/7-42 weeks). Umbilical cord (1.5 mL) and 24(±4) h of life (24 h) (1 mL) blood samples were collected for GSH, MDA, and ET-1 analyses. GSH, MDA, and ET-1 were determined using established methodology. Mean cord MDA levels for all age groups, Early Preterm (2.93 ± 0.08 pg/ml), Late Preterm (2.73 ± 0.15 pg/ml), and Term (2.92 ± 0.13 pg/ml), were significantly higher than those at 24 h of life (p < 0.001). Mean cord ET-1 levels were significantly higher than 24 h samples in both Early and Late Preterm groups (p < 0.05). Cord and 24 h ET-1 levels did not correlate with MDA and GSH levels at birth (r2 = 0.03, p > 0.05 and r2 = 0.001, p > 0.05, respectively) or 24 h of life (r2 = 0.001, p > 0.05 and r2 = 0.03, p > 0.05, respectively). Preterm neonates exposed to prenatal corticosteroids (1.87 ± 0.31 pg/ml) had lower cord MDA levels than non-exposed neonates (2.85 ± 0.12 pg/ml) (p < 0.05). Both cord and 24 h OS markers were significantly higher in neonates treated with oxygen therapy (p < 0.005 and p < 0.05, respectively) than those who did not receive supplemental oxygen. Oxidative stress markers (MDA and GSH) and ET-1 levels act independently. MDA is higher in cord blood than at 24 h of life regardless of gestational age. In preterm neonates, ET-1 levels are higher in umbilical cord blood compared to 24 h of life.